"I'm not sitting around doing nothing with my life": The aspirations of school-aged mothers. (2020) - Howell, Angelique; Lynch, Deborah
Highlights: These young mothers were highly motivated to complete school. The program, school and external agencies worked collaboratively to provide support. Some young mothers expressed the wish for more advanced learning options. Approximately half aspired to attend university at the time of the interview. A broader range of pathways may be achievable through youth-adult partnerships. Abstract: School-aged mothers face unique challenges in completing their formal schooling. This paper privileges the voices of young mothers in a qualitative study which explored a school-based young mothers' program in Queensland, Australia. While they perceived the program as supportive, some expressed the wish for more advanced learning options. This aligns with research that suggests young mothers are motivated to complete school and are seeking meaningful career pathways. The lens of intersectionality provides opportunities for deeper critical inquiry into the positioning of young mothers in society. How programs can offer flexible and challenging learning opportunities for young mothers who wish to pursue academic pathways remains a challenge. This identifies an area for future research to disrupt cycles of inequity and educational disadvantage.